The Effect of Laser Heating and Overcasting Deposition on the Efficiency of Plasmonic Solar Cell with Noble Metallic Nanostructures - Matrood, Haider M.; Ail, Nagham Thamer; Awaad, Amany Akram (Iraqi Journal of Science, 2021)
Surface plasmon resonance could increase the efficiency of solar cells , when light is trapped by the noble metallic nanoparticles arrangement at and into the silicon solar cell (SSC) surface. Pure noble metal (silver and gold) nanoparticles (NPs) have been synthesized as colloids in de-ionized water (DW) by pulsed laser ablation (PLA) process at optimum laser fluence. Silicon solar cell with low efficiency was converted to plasmonic silicon solar cell by overcasting deposition method of silver nanoparticles on the front side of the SSC. The performance of plasmonic solar cell (PSC) was increased due to light trapping. Two mechanisms were involved : inserting silver nanoparticles (Ag NPs) inside the silicon layer by the heating effect of pulsed laser and depositing gold nanoparticles (Au NPs) on the surface of the SSC by overcasting method. The optical properties of silver and gold colloidal solutions were studied with UV- Visible spectrophotometer with a range from 190 nm to 1100 nm. The absorption spectra showed single absorption peak located at about the characteristic value for silver and gold nanoparticles due to the surface plasmon resonance. Atomic Force Microscope (AFM) images were studied , the ablated noble NPs by pulsed laser have an average diameter less than 100 nm. AFM images showed the morphology of SSC surface without and with nanoparticles before and after overcasting and heating by laser methods. Electrical measurements for SSC namely current – voltage ( I-V )characteristics and responsivity (Rλ) displayed higher efficiency after these procedures. The efficiency rise to(5.2%) due to the localized surface plasmons excitation of (Ag NPs) that were embedded into the silicon layer by the heating effect of pulsed laser. The deposition of AuNPs on the silicon surface of the plasmonic SC additionally increased the efficiency to (7.28%), due to light trapping by scattering from Au NPs towards the plasmonic solar cell depth .